Amorphous silica powder and resin composition

By adjusting the particle size frequency distribution of amorphous silica powder and combining components such as epoxy resin, a resin composition with excellent fluidity and narrow gap filling ability is prepared, which solves the problem of insufficient fluidity of the resin composition in the prior art and is suitable for semiconductor sealants.

CN115968354BActive Publication Date: 2025-02-28DENKA CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180051557.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-08-25
Filing Date
2021-08-17
Publication Date
2025-02-28
Estimated Expiration
2041-08-17

AI Technical Summary

Technical Problem

In the prior art, the resin composition has insufficient fluidity in solid sealing technology, making it difficult to effectively fill the narrow gap under the semiconductor chip.

Method used

By adjusting the particle size frequency distribution of the amorphous silica powder, the frequency of particles with a particle size of 0.50-1.83 μm is less than 3.0% by adjusting the particle size of the amorphous silica powder. Combining an epoxy resin, a curing agent and a curing accelerator, a resin composition containing 80-90% amorphous silica powder is prepared.

Benefits of technology

The fluidity and narrow gap fillability of the resin composition are significantly improved, making it suitable for the application of semiconductor sealant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004087995450000081
    Figure BDA0004087995450000081
  • Figure BDA0004087995450000111
    Figure BDA0004087995450000111
Patent Text Reader

Abstract

The present invention provides an amorphous silica powder suitable for obtaining a solid sealing material having excellent fluidity and filling properties and a resin composition filled with the amorphous silica powder. More specifically, in the present invention, the amorphous silica powder is prepared in such a manner that the most frequent particle size in the particle size frequency distribution is in the range of 1 to 10 μm and the frequency of particles with a particle size of 0.50 to 1.83 μm in the particle size frequency distribution is less than 3.0%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an amorphous silicon dioxide powder suitable for use as a solid sealing material and a resin composition containing the amorphous silicon dioxide powder. Background Art

[0002] Generally, a semiconductor device in which a semiconductor chip mounted on a substrate is sealed with a resin is well known. As a technology to meet the demand for further miniaturization, thinning, and high density of such a semiconductor device, a flip chip connection method is known.

[0003] Patent Document 1 discloses a technology related to a flip-chip connection method. In the case of this flip-chip connection method, two processes are required: bottom filling of a narrow gap and overmolding of the entire chip. Therefore, a technology (solid sealing technology) is being developed that uses only a non-liquid epoxy resin composition to fill the narrow gap under the chip and seal the entire chip at the same time. For this development, the fluidity of the resin composition is a problem (Patent Document 2).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent No. 3695521

[0007] Patent Document 2: Japanese Patent Application Publication No. 2011-132268 Summary of the invention

[0008] The present invention provides an amorphous silica powder having excellent fluidity and suitable for solid sealing, and a resin composition containing the amorphous silica powder.

[0009] The present inventors have succeeded in solving the above-mentioned problem by making the frequency of particles with a particle size of 0.50 to 1.83 μm less than 3.0% in the particle size frequency distribution, with the most frequent particle size being in the range of 1 to 10 μm.

[0010] That is, in one aspect, the present invention provides an amorphous silica powder characterized in that the mode particle size in the particle size frequency distribution is in the range of 1 to 10 μm, and the frequency of particles with a particle size of 0.50 to 1.83 μm in the particle size frequency distribution is less than 3.0%.

[0011] The amorphous silicon dioxide powder of the present invention has a particle size of 1 to 12 m 2 The specific surface area is preferably 3 to 10.5 m 2 / g.

[0012] The amorphous silica powder of the present invention has an on-sieve cumulative distribution of particles having a particle size of 13 μm or more of 1% by mass or less.

[0013] Furthermore, the amorphous silica powder of the present invention has a melting rate of 95% or more, and a total concentration of uranium and thorium elements of 10 ppb or less.

[0014] In another aspect, the present invention also provides a resin composition for solid sealing comprising the amorphous silicon dioxide powder of the present invention, an epoxy resin, a curing agent and a curing accelerator.

[0015] The resin composition of the present invention is characterized by containing 80 to 90% by mass of the amorphous silica powder.

[0016] The resin composition containing the amorphous silica powder of the present invention is excellent in flow characteristics such as spiral flow and narrow gap filling ability, and is therefore particularly useful as a semiconductor sealing agent. DETAILED DESCRIPTION

[0017] Hereinafter, the present invention will be described in further detail. However, the present invention is not limited to the following embodiments.

[0018] <Amorphous silica powder>

[0019] The amorphous silica powder of the present invention can improve fluidity by having a mode particle size in the range of 1 to 10 μm in the particle size frequency distribution and having a frequency of particles with a particle size of 0.50 to 1.83 μm of less than 3.0% in the particle size frequency distribution.

[0020] In the particle size frequency distribution of the amorphous silica powder of the present invention, the most frequent particle size is in the range of 1 to 10 μm. If the most frequent particle size in the particle size frequency distribution of the amorphous silica powder exceeds 10 μm, the above-mentioned problem occurs. On the other hand, in a powder with a small particle size such as the most frequent particle size in the particle size frequency distribution being less than 1 μm, the viscosity of the semiconductor sealing material becomes too high, and the filling amount of the powder cannot be increased. The lower limit may be above 1.5 μm, above 2.0 μm, above 2.5 μm, above 3.0 μm, or above 3.2 μm. The upper limit may be below 8.0 μm, below 7.0 μm, below 6.0 μm, below 5.0 μm, below 4.2 μm, or below 4.0 μm. In the particle size frequency distribution of the amorphous silica powder of the present invention, for example, the most frequent particle size is in the range of 3.0 to 4.2 μm. The mode particle size here refers to the particle size showing the highest frequency in the particle size distribution of the powder obtained by the measurement method described below. When the mode particle size of the raw material amorphous silica powder exceeds 10 μm, classification is performed to adjust the particle size distribution.

[0021] In addition, in the peak with a maximum value in the range of 1 to 10 μm, if the frequency of particles with a particle size of 0.50 to 1.83 μm is less than 3.0% by volume, the fluidity of the amorphous silica powder can be further improved. It is more preferably less than 2.5%, less than 2.0%, less than 1.5%, less than 1.0%, less than 0.5%, and can be 0.0%. The method of making the frequency of particles with a particle size of 0.50 to 1.83 μm less than 3.0% can adopt a method known in the past, for example, a method of removing the coarse powder side and the fine powder side using a precision wind classifier can be exemplified. It should be noted that the frequency of particles with a particle size of 0.50 to 1.83 μm is a value obtained by the particle size distribution measurement method described later.

[0022] From the viewpoint of obtaining the effects of the present invention, the number of peaks showing a maximum frequency in the range of 1 to 10 μm in the particle size frequency distribution may be one or a plurality of peaks.

[0023] The frequency at the maximum value of the peak of the most frequent particle size showing a maximum frequency in the range of 1 to 10 μm in the particle size frequency distribution may be 5% by volume or more. The lower limit of the frequency may be 9% by volume or more. The upper limit of the frequency may be 20% by volume or less, 15% by volume or less, or 14.5% by volume or less.

[0024] The specific surface area is preferably set to 1 to 12 m 2 / g. In particular, in the present invention, since the frequency of particles with a particle size of 0.50 to 1.83 μm is less than 3.0%, there is a tendency for the specific surface area to decrease. Therefore, it is preferred to add ultrafine powder of 0.5 μm or less to increase the specific surface area. The size of the preferred ultrafine powder is 0.1 to 0.5 μm in terms of median diameter. In the case of amorphous silica powder with a specific surface area of ​​more than 12 m 2 / g, the tendency of aggregation between particles increases and the fluidity of the semiconductor sealing material decreases. The upper limit may be 10.5m 2 / g or less, can be 9m 2 / g or less, can be 8m 2 / g or less. On the other hand, when the specific surface area is less than 1m 2 When the powder has a density of 200 μg / cm2, it becomes difficult for the powder to form a close-packed structure, so the fluidity of the semiconductor sealing material decreases. More preferably, the powder has a density of 200 μg / cm2. 2 / g or more, more preferably 3m 2 / g or above.

[0025] In the amorphous silica powder of the present invention, d10, d50, and d90 are not particularly limited. d10 can be 0.5 to 4.0 μm. d50 can be 3.5 to 7.0 μm. d90 can be 4.0 to 9.0 μm. However, from the viewpoint of obtaining the effect of the present invention, d10 is preferably 1.5 to 3.5 μm. d50 is preferably 3.0 to 5.0 μm. d90 is preferably 4.0 to 7.0 μm. Here, d10, d50, and d90 are the particle sizes when the cumulative values ​​in the cumulative distribution of particle sizes are 10%, 50%, and 90%, respectively. For amorphous silica powder, the particle size distribution is obtained by the method described later, expressed as volume distribution, and the refractive index is set to 1.5.

[0026] The amorphous silica powder of the present invention can make the cumulative distribution of particles having a particle size of 13 μm or more be 1% by mass or less and 0% by mass. By reducing the number of coarse particles, the amorphous silica powder can more easily form a close-packed structure, and the fluidity of the semiconductor sealing material is improved.

[0027] The amorphous silica powder of the present invention may contain other components (additives, etc.) other than the amorphous silica powder within the range that does not impair the effect of the present invention. For example, the other components may be 5% by mass or less, 3% by mass or less, 1% by mass or less, or 0% by mass.

[0028] In addition, depending on the application, the amorphous silica powder of the present invention preferably does not contain uranium and thorium as other components. When used in a semiconductor sealing material for sealing a semiconductor, the total concentration of uranium and thorium is preferably 10 ppb or less from the perspective of suppressing the failure rate of memory rewriting.

[0029] From the viewpoint of making the thermal expansion coefficients of the semiconductor chip and the semiconductor sealing material close, the amorphous silica powder of the present invention is most preferably amorphous silica powder produced by melting crystalline silica at high temperature or by a synthetic method. Therefore, the melting rate of the amorphous silica powder of the present invention is preferably 95% or more.

[0030] The shape of the amorphous silica powder may be any of spherical, crushed, needle-shaped, flake-shaped, etc., but spherical amorphous silica powder is preferred from the viewpoint of filling as much as possible and reducing the thermal expansion coefficient of the semiconductor sealing material.

[0031] The amorphous silica powder of the present invention may be mixed with other inorganic fillers. Here, other inorganic fillers include different types of materials such as alumina powder and magnesia powder, as well as materials with different particle size distributions even if they are the same amorphous silica powder.

[0032] The particle size distribution of the amorphous silica powder of the present invention is measured using a Coulter particle size distribution analyzer LS13 320 (Beckman Coulter, Inc.) Regarding the measurement conditions, a silica aqueous solution pre-dispersed with an ultrasonic homogenizer is placed in the device and analyzed under the condition of a refractive index of 1.5.

[0033] In order to produce the amorphous silicon dioxide powder of the present invention, it can be carried out by mixing or classifying appropriate amounts of powders having different particle sizes. In industry, it is preferred to use a classifier for classification, and the classification operation can be any of a dry method and a wet method. It should be noted that from the viewpoint of productivity and removal of coarse particles, it is preferred to use a dry precision wind classifier.

[0034] <Resin composition>

[0035] Next, the resin composition of the present invention will be described.

[0036] It is believed that the improvement in fluidity of the present invention is due to the interaction between particles being adjusted by adjusting the particle size distribution. Therefore, no matter how the type of resin is, the effect of improving fluidity can be obtained. Therefore, it can be used not only for the resin composition for solid sealing, but also for the improvement in fluidity of the resin composition for liquid sealing. However, since the amorphous silicon dioxide powder of the present invention is suitable for solid sealing, the resin for solid sealing is described below. It should be noted that the non-liquid resin composition used in solid sealing is, for example, a resin composition that is solid at room temperature, such as a powdery, granular, tablet-shaped tablet, etc.

[0037] The resin composition for solid sealing contains a resin, a curing agent, an inorganic filler and a curing accelerator. Each component is described below.

[0038] For solid sealing, epoxy resin is preferably used as resin. As epoxy resin, epoxy resin used in the past in the technical field of epoxy resin composition for sealing can be used without restriction. As such epoxy resin, for example, phenol novolac type epoxy resin, cresol novolac type epoxy resin, bisphenol type epoxy resin, distyrene type epoxy resin, trisphenol methane type epoxy resin, phenol aralkyl type epoxy resin, naphthol type epoxy resin, naphthalene type epoxy resin, biphenyl type epoxy resin, dicyclopentadiene type epoxy resin, phenylene type epoxy resin and triphenylmethane type epoxy resin etc. can be cited. They can be used alone or in combination of two or more.

[0039] The content of the epoxy resin in the resin composition may be 2 to 15% by mass.

[0040] As the curing agent, the curing agent used in the technical field of the epoxy resin composition for sealing can be used without limitation. As such a curing agent, for example, various polyphenol compounds or naphthol compounds such as phenol novolac resin, cresol novolac resin, phenol aralkyl resin, naphthol aralkyl resin, biphenyl aralkyl resin, etc. can be cited. They can be used alone or in combination of two or more.

[0041] The mixing ratio of epoxy resin to curing agent (epoxy resin / curing agent) is preferably 0.5 to 1.5, more preferably 0.8 to 1.2 in terms of equivalent ratio. If the mixing ratio is too small, there will be too much curing agent and it will be economically disadvantageous, and if the mixing ratio is too large, there will be too little curing agent and insufficient curing.

[0042] As the curing accelerator, a curing accelerator conventionally used in the technical field of the epoxy resin composition for sealing can be used without limitation. Examples of such a curing accelerator include imidazoles such as 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-methyl-4-ethylimidazole, 2-phenylimidazole, and 2-methyl-4-methylimidazole, tertiary amines such as 1,8-diazabicyclo[5.4.0]undecene-7, triethylenediamine, and benzyldimethylamine, triphenylphosphine, tributylphosphine, and tetraphenylphosphine. Organic phosphines such as tetraphenylborate, and microencapsulated organic phosphines, etc. These may be used alone or in combination of two or more.

[0043] The content of the curing accelerator is preferably 1 to 10 parts by mass or less relative to 100 parts by mass of the total content of the epoxy resin and the curing agent. When the content of the curing accelerator is less than 1 part by mass, the curing acceleration function cannot be well exerted, and when the content of the curing accelerator is more than 10 parts by mass, it is possible to produce a defect in the formability. It is preferably 2 to 4 parts by mass.

[0044] As the inorganic filler, the amorphous silica powder of the present invention is used, and the content thereof is preferably 80 to 90% by mass, more preferably 83 to 90% by mass, and even more preferably 86 to 90% by mass.

[0045] In addition, the resin composition of the present invention may further contain other additives such as coupling agents, release agents, colorants, flame retardants, ion traps, and flexibilizers as other ingredients. As coupling agents that can be used in this embodiment, for example, aminosilanes such as γ-aminopropyl triethoxysilane, N-phenyl-γ-aminopropyl trimethoxysilane, mercaptosilanes such as mercaptopropyl trimethoxysilane, glycidoxysilanes such as γ-glycidoxypropyl trimethoxysilane, and γ-glycidoxypropyl triethoxysilane can be cited. They can be used alone or in combination of two or more. As release agents that can be used in this embodiment, for example, waxes with high melting points such as carnauba wax and montan wax, higher fatty acids such as stearic acid and their salts, esters, or carboxyl-containing polyolefins can be cited. They can be used alone or in combination of two or more. As colorants that can be used in this embodiment, for example, carbon black, various pigments, etc. can be cited. As the flame retardant that can be used in the present embodiment, a halogen-free or antimony-free flame retardant is preferred, for example, metal hydroxides (metal hydrates) such as magnesium hydroxide, aluminum hydroxide or calcium hydroxide can be cited. The content of these other additives in the epoxy resin composition is appropriately determined as long as it is within the range of the function of each additive that is well exerted, but for example, in the epoxy resin composition total amount, it is within the range of 0.01 to 5 mass %. In addition, the total of these other components and impurities can be less than 10 mass %, can be less than 8 mass %, can be less than 5 mass %, can be less than 3 mass %.

[0046] The non-liquid epoxy resin composition is prepared, for example, as follows. That is, epoxy resin, curing agent, inorganic filler, curing accelerator and other components are respectively matched in prescribed amounts, uniformly mixed with a mixer, a stirrer, etc., and then heated and kneaded with a kneader, a roller, etc. After kneading, it is cooled and solidified, and crushed into a prescribed particle size to obtain a powdery or granular epoxy resin composition that is solid at room temperature. If necessary, it can be made into a tablet by further tabletting.

[0047] Hereinafter, a method of using the resin composition for solid sealing of the present invention will be described.

[0048] In this embodiment, a semiconductor device (not a device of flip-chip connection) is manufactured as follows. That is, a semiconductor chip is mounted on a semiconductor chip mounting substrate, the substrate and the semiconductor chip are electrically connected with a gold wire (wire bonding), and then the semiconductor chip on the substrate is sealed with the resin composition of the present invention. In order to perform this sealing, transfer molding using a mold can be adopted.

[0049] In this embodiment, a semiconductor device of flip-chip connection is made, for example, as follows. That is, a protruding electrode (bump) is formed on the circuit surface of the semiconductor chip, and is directly connected to the electrode terminal of the semiconductor chip mounting substrate in a flip-chip manner, and then the semiconductor chip on the substrate is sealed with the resin composition of the present invention. That is, a molded bottom filling is performed to fill the narrow gap under the chip and seal the entire chip. In order to perform this sealing, transfer molding using a mold can be used.

[0050] Example

[0051] <Preparation of amorphous silicon dioxide powder>

[0052] The amorphous silica powder of the preparation example of the present invention was prepared according to the following steps. It should be noted that commercially available amorphous silica was used as a raw material. It should be noted that the raw material had a peak with a most frequent particle size in the range of 1 to 10 μm.

[0053] [Coarse powder classification]

[0054] In this embodiment, in order to remove large particles, the raw material amorphous silica powder was coarsely classified. The cumulative distribution of particles with a particle size of 13 μm or more is shown in Table 2. It should be noted that in the embodiment, the cumulative distribution of particles with a particle size of 13 μm or more is 0.0 mass %.

[0055] [Micro powder classification]

[0056] Next, the cumulative value of particles with a particle size of 0.50 to 1.83 μm was adjusted by removing the fine powder side using a precision air classifier. The cumulative value of particles with a particle size of 0.50 to 1.83 μm is shown in Table 2. It should be noted that in the examples, the frequency at the most frequent particle size in the range of 1 to 10 μm was 9.3 to 14.3% by volume.

[0057] [Ultrafine powder compounding]

[0058] Next, amorphous silica powder having a small particle size (ultrafine powder having a median diameter of 0.19, 0.28 or 0.37 μm) was blended with the amorphous silica powder obtained in the steps up to the fine powder classification at the internal addition ratio shown in Table 2.

[0059] <Preparation of resin composition>

[0060] An epoxy resin, a curing agent, an inorganic filler, a curing accelerator and other materials are mixed in the proportion (mass %) shown in Table 1, homogenized, heated with a biaxial roller heated to 80° C., kneaded, extruded, cooled and cured, and then crushed into a specified particle size with a pulverizer to prepare a powdered epoxy resin composition that is solid at room temperature.

[0061] [Table 1]

[0062]

[0063] <Evaluation of amorphous silica powder and resin composition>

[0064] The property values ​​of the obtained amorphous silica powder and the resin composition were measured as follows. The measurement methods were as follows.

[0065] [Evaluation of amorphous silica particles]

[0066] (1) Specific surface area

[0067] The BET theory is applied to the adsorption isotherm measured by the gas adsorption method to determine the specific surface area (BET value) (BET method).

[0068] (2) Particle size

[0069] The particle size frequency distribution and particle size cumulative distribution of the micropowder were determined using the Coulter method which is not affected by the sample density.

[0070] The median diameter d (μm) of the ultrafine powder is determined by the BET value measured using the BET method based on the relative density of the silica particles (density 2.2 g / cm 3 ) is calculated using the following mathematical formula:

[0071] [Mathematical formula 1]

[0072] Median diameter d = 6 / ((BET value)*2.2).

[0073] (3) Melting rate

[0074] The melting rate in the present invention can be measured by using a powder X-ray diffraction device to perform X-ray diffraction analysis of the sample in the range of 26° to 27.5° of 2θ of CuKα rays, based on the intensity ratio of specific diffraction peaks. That is, crystalline silica has a main peak at 26.7°, but molten silica does not exist at this position. When molten silica and crystalline silica are mixed, a peak height of 26.7° corresponding to their ratio can be obtained. Therefore, the crystalline silica mixing ratio can be calculated from the ratio of the X-ray intensity of the sample to the X-ray intensity of the crystalline silica standard sample (X-ray intensity of the sample / X-ray intensity of crystalline silica), and the melting rate can be calculated using the following formula:

[0075] [Mathematical formula 2]

[0076] Melting rate (%) = (1-crystalline silica mixing ratio) × 100

[0077] (4) Concentration of uranium and thorium

[0078] The contents of uranium and thorium were measured using an inductively coupled plasma mass spectrometer (ICP-MS) to calculate the concentrations in the powder.

[0079] [Evaluation of resin composition]

[0080] The prepared powdered epoxy resin composition was used to perform transfer molding under the following conditions, thereby evaluating spiral flow and narrow gap filling properties.

[0081] (5) Spiral flow

[0082] (condition)

[0083] ·Mold size: φ3mm spiral shape

[0084] Mold temperature: 175℃

[0085] Injection pressure: 65kgf / cm 2

[0086] Molding time: 90 seconds

[0087] (6) Narrow gap filling

[0088] (condition)

[0089] Mold size: 5×60×0.02mm

[0090] Mold temperature: 175℃

[0091] Injection pressure: 65kgf / cm 2

[0092] Molding time: 90 seconds

[0093] [Evaluation results]

[0094] Table 2 shows the physical property values ​​of the preparation conditions (powder classification conditions, blending) of each amorphous silica powder, powder properties, and flow properties (spiral flow, narrow gap filling property) of the resin composition using each amorphous silica powder.

[0095] [Table 2]

[0096]

[0097] Industrial Applicability

[0098] The resin composition filled with the amorphous silica powder of the present invention has excellent fluidity and filling properties and is therefore suitable for a sealant for semiconductor devices. The resin composition has a particle size frequency distribution in which the most frequent particle size is in the range of 1 to 10 μm and the frequency of particles with a particle size of 0.50 to 1.83 μm in the particle size frequency distribution is less than 3.0%.

Claims

1. An amorphous silicon dioxide powder, characterized in that: The most frequent particle size in the particle size frequency distribution is in the range of 1 to 10 μm, and the frequency of particles with a particle size of 0.50 to 1.83 μm in the particle size frequency distribution is less than 3.0%; The amorphous silicon dioxide powder has a particle size of 1 to 12 m 2 / g specific surface area.

2. The amorphous silicon dioxide powder according to claim 1, wherein The cumulative distribution of particles having a particle size of 13 μm or more was 1% by mass or less.

3. The amorphous silicon dioxide powder according to claim 1 or 2, wherein The melting rate is more than 95%.

4. The amorphous silicon dioxide powder according to claim 1 or 2, wherein The total concentration of uranium and thorium is 10 ppb or less.

Citation Information

Patent Citations

  • Epoxy resin composition and semiconductor device

    JP2011132268A

  • Preparation method of ultrahigh-purity amorphous spherical silica powder

    CN104556076A

  • Preparation method of low-radioactivity amorphous spherical silica micropowder

    CN110950345A